Lignin-based self-repairing thermoelectric hydrogel, thermoelectric conversion device and preparation method and application thereof
A self-healing thermoelectric hydrogel was prepared by combining lignin sulfonate modified with cyclodextrin, adamantane acrylate, and inorganic small molecule thermoelectric materials. This solved the problems of low tensile properties and conversion efficiency of hydrogel thermoelectric materials, and achieved efficient thermoelectric conversion and excellent electrochemical performance.
Patent Information
- Application Number
- CN202411459264.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The tensile properties of existing hydrogel thermoelectric materials need to be improved, and they suffer from low thermoelectric conversion efficiency, poor electrochemical performance, and long preparation cycles.
A lignin-based self-healing thermoelectric hydrogel was prepared by combining cyclodextrin-modified lignin sulfonate with adamantane acrylate and specific inorganic small molecule thermoelectric materials such as lithium chloride. The hydrogel forms a network structure through cross-linking, which enhances its mechanical properties and self-healing ability.
This improves the mechanical properties, self-healing ability, and temperature-sensitive properties of thermoelectric hydrogels, enhances the thermal effect and electrochemical performance of thermoelectric conversion devices, and simplifies the preparation process.
Smart Images

Figure CN119285874A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermoelectric conversion, and more specifically, relates to a lignin-based self-repairing thermoelectric hydrogel, a thermoelectric conversion device, and a preparation method and application thereof. Background Art
[0002] Against the backdrop of the continued growth of global energy demand and increasingly serious environmental problems, the study of energy conversion technology has become one of the most urgent scientific issues at present. As a green and environmentally friendly new energy, low-grade thermal energy shows great potential among many renewable energy sources. Low-grade thermal energy with a temperature difference of <100 °C in the living environment, industrial production processes, solar energy and the human body is an energy source with great application potential. Converting this waste heat into usable electrical energy will help slow down the consumption of non-renewable energy, thereby helping to reduce greenhouse gas emissions. Using the thermoelectric effect is an effective way to directly convert waste heat in the environment into electrical energy, which can then drive personal medical electronic devices, which is of great significance to smart wearable medical devices.
[0003] In recent years, conventional thermoelectric materials have made some progress in electron diffusion and electron Seebeck effect, but their widespread application is limited by the scarcity or toxicity of raw materials, complex processing, high cost and poor mechanical flexibility. In addition, the electron Seebeck coefficient of conventional thermoelectric materials is usually low, only reaching μV•K -1 level. In contrast, ionic thermoelectric materials, as new thermoelectric conversion materials, show significant advantages. Their ionic Seebeck coefficient is 2 to 3 orders of magnitude higher, and they can effectively collect low-grade thermal energy. This material has low cost, excellent performance, high Seebeck coefficient, low thermal conductivity and easy processability, so it is regarded as a promising green energy conversion material. However, ionic thermoelectric materials also have some shortcomings. For example, Chinese patent application CN115895158A discloses a thermoelectric conversion material and a thermoelectric conversion device. The thermoelectric conversion material has temperature sensitivity and a high Seebeck coefficient. The thermoelectric conversion device assembled with polyaniline / carbon cloth electrodes has an area capacitance of up to 750 mF / cm 2 However, its energy density output in 1 hour is only 88 J / m 2 , which severely limits its electrochemical performance. In addition, Chinese patent application CN111564316A discloses a gel electrode and a fully gel-state ionic thermoelectric supercapacitor, with a maximum volumetric capacitance of 983.6 mF / cm 3 However, its maximum Seebeck coefficient is only 3.6 mV / K, the thermoelectric conversion efficiency is low, the device preparation cycle is long, and the tensile properties of the gel electrode loaded with electrolyte need to be further improved. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the existing hydrogel thermoelectric materials, such as the need to further improve the tensile properties of the materials, and the low thermoelectric conversion efficiency, poor electrochemical properties and long preparation cycle of the thermoelectric conversion devices prepared based on the hydrogels, and to provide a method for preparing a self-repairing thermoelectric hydrogel based on lignin.
[0005] Another object of the present invention is to provide the above-mentioned lignin-based self-repairing thermoelectric hydrogel.
[0006] Another object of the present invention is to provide a thermoelectric conversion device.
[0007] Another object of the present invention is to provide applications of the above-mentioned lignin-based self-repairing thermoelectric hydrogel or the above-mentioned thermoelectric conversion device in the fields of wearable thermoelectric conversion devices, the Internet of Things, and sensing.
[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions: The present invention protects a method for preparing a lignin-based self-repairing thermoelectric hydrogel, comprising the following steps: Cyclodextrin-modified lignin sulfonate and adamantyl acrylate are added to a solvent containing an inorganic small molecule thermoelectric material and mixed evenly, and unsaturated carboxylic acid monomers, acrylamide monomers, metal ions and initiators are added to fully react to prepare a lignin-based self-healing thermoelectric hydrogel; Wherein, the inorganic small molecule thermoelectric material is selected from one or more of lithium chloride, sodium chloride and potassium chloride.
[0009] The present invention successfully prepares a self-repairing thermoelectric hydrogel based on lignin by compounding a specific inorganic small molecule thermoelectric material with cyclodextrin-modified lignin sulfonate and adamantyl acrylate. The inorganic small molecule thermoelectric material can not only enhance the interaction between polymer chains (such as ionic bonds and hydrogen bonds), but also help maintain the stability of the network structure and improve the mechanical strength of the hydrogel. Specifically, the thermoelectric hydrogel uses unsaturated carboxylic acid monomers and acrylamide monomers as the skeleton of the hydrogel, and at the same time uses the structural characteristics of cyclodextrin-modified lignin sulfonate (LS-CD) to introduce host-guest interactions, and the phenolic hydroxyl groups in LS-CD cooperate with metal ions to form a metal ion chelated redox pair as a "cross-linking agent" and "catalyst". Through the joint action of these components, copolymerization and cross-linking are obtained to obtain a self-repairing thermoelectric hydrogel based on lignin. The thermoelectric hydrogel prepared by the above method has excellent mechanical properties, temperature-sensitive properties and self-repairing ability.
[0010] Furthermore, the preparation method of the cyclodextrin modified lignin sulfonate comprises the following steps: S1. Add cyclodextrin, p-toluenesulfonyl imidazole and alkaline reagent into water and mix well. After filtering, adjust the pH of the filtrate to 7-8, react fully, and post-treat to obtain the intermediate product CDOTs. S2. Add the CDOTs and lignin sulfonate obtained in step S1 into water and mix well, raise the temperature to 70-80°C for sufficient reaction, and post-treat to obtain cyclodextrin-modified lignin sulfonate.
[0011] Furthermore, in step S1, the cyclodextrin includes one or more of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin. Cyclodextrin-modified lignin sulfonates obtained from cyclodextrins with different crystal structures can prepare thermoelectric hydrogels with good performance. Among them, β-cyclodextrin has a moderate inner diameter and is more suitable for inclusion of hydrophobic molecules (such as adamantane), thereby improving its solubility and stability, which is conducive to the subsequent construction of a hydrogel with a stable structure. Therefore, the cyclodextrin is preferably β-cyclodextrin.
[0012] Furthermore, in step S1, the mass ratio of cyclodextrin to p-toluenesulfonyl imidazole is (1.5-10): (1-3).
[0013] Furthermore, in step S1, the mass ratio of cyclodextrin to p-toluenesulfonyl imidazole is (1.5-10):1.
[0014] Furthermore, in step S1, the mixing is stirring mixing.
[0015] Furthermore, the stirring and mixing time is 2 to 4 hours.
[0016] Furthermore, in step S1, the pH is adjusted by using hydrochloric acid.
[0017] Furthermore, in step S1, the precipitation time is 18 to 36 hours.
[0018] Furthermore, in step S1, the post-treatment includes filtration, washing and recrystallization.
[0019] Furthermore, the filtering is to filter the precipitated material and collect the filter residue.
[0020] Furthermore, the washing is to wash the collected filter residue with ice water and acetone in sequence for 3 to 5 times.
[0021] Furthermore, the recrystallization is to remove soluble impurities by recrystallizing the washed filter residue with hot water at 80-100°C, and repeating the process 2-3 times.
[0022] Specifically, in step S1, the post-treatment includes filtering the precipitated material, collecting the filter residue, washing the filter residue with ice water and acetone for 3 to 5 times in sequence, collecting the washed filter residue and then recrystallizing it with hot water at 80 to 100°C to remove soluble impurities, repeating 2 to 3 times, and the product obtained after recrystallization is the intermediate product CDOTs.
[0023] Furthermore, in step S2, the mass ratio of the CDOTs to the lignin sulfonate is 1:(0.67-2.5).
[0024] Furthermore, in step S2, the mixing time is 1 to 2 h.
[0025] Furthermore, in step S2, the sufficient reaction time is 48 to 72 hours.
[0026] Furthermore, in step S2, the post-treatment includes dialysis and drying.
[0027] Furthermore, the dialysis is to dialyze the cooled mixture and collect the retained fluid.
[0028] Furthermore, the drying is to dry the retained solution after dialysis, and the drying is preferably freeze drying.
[0029] Specifically, in step S2, the post-treatment includes dialyzing the cooled mixture, and freeze-drying the retained solution after the dialyzate to obtain cyclodextrin-modified lignin sulfonate.
[0030] Further, as a preferred embodiment, the preparation method of adamantyl acrylate comprises the following steps: Si. adding adamantane alcohol and triethylamine to an organic solvent and mixing to obtain a mixed solution; Sii. Dilute acryloyl chloride with an organic solvent and dropwise add it into the mixed solution obtained in step Si to mix well, and then post-treat to obtain adamantyl acrylate.
[0031] Furthermore, in step Si, the adamantane alcohol is 1-adamantanol and / or 2-adamantanol.
[0032] Preferably, the adamantane alcohol is 1-adamantanol, which has stronger reactivity and is more likely to undergo nucleophilic substitution reaction with acryloyl chloride to form corresponding esters or amino compounds.
[0033] Furthermore, in step Si, the mass ratio of adamantane alcohol to triethylamine is 1:(1-3).
[0034] Furthermore, in step Si, the mixing time is 15 to 40 min.
[0035] Furthermore, in step Sii, the mass ratio of the acryloyl chloride to the organic solvent is 1:(1.67-10).
[0036] Furthermore, in step Sii, the mixing time is 18 to 36 hours.
[0037] Furthermore, in step Sii, the post-treatment includes filtration, washing, concentration and purification.
[0038] Furthermore, the filtration is to filter the mixed solution and collect the filtrate.
[0039] Furthermore, the washing is washing the filtrate with ice water and acetone for 1 to 3 times.
[0040] Furthermore, the concentration is to collect the organic phase after washing and to carry out low-temperature reduced-pressure rotary evaporation concentration at 4-15°C.
[0041] Furthermore, the purification is to purify the concentrated material using column chromatography, and the eluent is V 乙酸乙酯 :V 正己烷 =1:(15~20).
[0042] Specifically, in step Sii, the post-treatment includes filtering the mixed solution, collecting the filtrate, washing the filtrate with ice water and acetone for 3 times, collecting the washed organic phase and concentrating it by low-temperature vacuum rotary evaporation at 4-15 °C, and purifying the concentrated substance by column chromatography, and the eluent is V 乙酸乙酯 :V 正己烷 =1:(15~20).
[0043] Furthermore, the mass ratio of the cyclodextrin-modified lignin sulfonate and adamantyl acrylate is (1-75): 1. The cyclodextrin-modified lignin sulfonate is used as a catalyst and a physical crosslinking agent, and adamantyl acrylate is used as a chemical crosslinking agent for the network structure. The crosslinking density at this mass ratio is more appropriate, and the mechanical properties of the prepared material are more excellent.
[0044] Furthermore, the mass ratio of the cyclodextrin modified lignin sulfonate to adamantyl acrylate is (1-40):1.
[0045] Preferably, the mass ratio of the cyclodextrin modified lignin sulfonate to adamantyl acrylate is 1:0.18.
[0046] Preferably, the inorganic small molecule thermoelectric material is lithium chloride. Lithium chloride exhibits excellent thermoelectric performance, specifically a high thermoelectric figure of merit (i.e., ZT, ZT=σS²T / κ, where σ is electrical conductivity, S is Seebeck coefficient, T is temperature, and κ is thermal conductivity) and good thermal stability, and it has the characteristics of low cost and easy access, so the inorganic small molecule thermoelectric material is preferably lithium chloride.
[0047] Furthermore, the concentration of the inorganic small molecule thermoelectric material is 0.1-3 mol / L.
[0048] Furthermore, the solvent is water and / or an organic solvent.
[0049] Furthermore, the organic solvent includes one or more of glycerol, propylene glycol, sugar ammonium salt ionic liquid, pyridine ionic liquid, and phosphate ionic liquid. Adding organic solvent to the hydrogel can effectively enhance its moisture retention performance and slow down water loss, thereby improving the stability and efficiency of the thermoelectric conversion device.
[0050] Preferably, the solvent is an aqueous glycerol solution.
[0051] More preferably, in the glycerol aqueous solution, the mixing ratio of glycerol and water is as follows: 甘油 :V 水 =1: (1~5).
[0052] Furthermore, the mixing time is 30 to 60 min.
[0053] Furthermore, the unsaturated carboxylic acid monomer is C3-C8 olefinic acid and / or C3-C8 acetylenic acid.
[0054] Furthermore, the unsaturated carboxylic acid monomer is C3-C5 olefinic acid and / or C3-C5 acetylenic acid.
[0055] Furthermore, the unsaturated carboxylic acid monomer includes one or more of acrylic acid, methacrylic acid, crotonic acid, propiolic acid, and butyric acid.
[0056] Furthermore, the acrylamide monomers include one or more of acrylamide, methacrylamide, and ethyl acrylamide.
[0057] Furthermore, the mass ratio of the unsaturated carboxylic acid monomer to the acrylamide monomer is 1:(0.8-1.5).
[0058] Furthermore, the metal ions are derived from one or more of stannous chloride, ferric chloride, calcium chloride, barium chloride, aluminum chloride, cobalt chloride, nickel chloride, cupric chloride, and silver chloride.
[0059] Preferably, the metal ion is stannous chloride. In the method for rapidly preparing multifunctional thermoelectric hydrogels in a metal-phenolic chemical system, compared with other transition metals (such as iron, cobalt, nickel, etc.), the introduction of stannous ions not only makes the hydrogel more uniform, but also significantly enhances its tensile properties.
[0060] Furthermore, the initiator is ammonium persulfate and / or potassium persulfate.
[0061] Furthermore, the sufficient reaction is that the cyclodextrin-modified lignin and the metal ions form a redox coordination system that can activate the initiator and quickly prepare the hydrogel.
[0062] The present invention protects the lignin-based self-repairing thermoelectric hydrogel prepared by the above preparation method.
[0063] The present invention utilizes the reducing property of lignin to quickly and efficiently construct a self-repairing hydrogel, solving the problem of the difficulty in balancing the self-repairing properties and mechanical properties of the self-repairing hydrogel. At the same time, specific inorganic small molecule thermoelectric materials are directly used to prepare a hydrogel with phase transition behavior, so that it has good self-repairing properties, mechanical properties and temperature-sensitive properties.
[0064] The present invention protects a thermoelectric conversion device, which includes the lignin-based self-repairing thermoelectric hydrogel and an electrode; the lignin-based self-repairing thermoelectric hydrogel is connected to the electrode as a thermoelectric conversion material.
[0065] The lignin-based self-repairing thermoelectric hydrogel used in the present invention has the advantages of high Seebeck coefficient and high thermoelectric conversion efficiency as an ionic thermoelectric material due to its volume phase transition behavior. The self-repairing thermoelectric hydrogel and electrodes are assembled into a thermoelectric conversion device, which can effectively convert thermal energy into electrical energy, achieve high thermal power and output power, and have excellent electrochemical performance.
[0066] Furthermore, the thermoelectric conversion device includes a stacked structure arranged in sequence: a first electrode, a thermoelectric conversion material, and a second electrode.
[0067] Furthermore, as a preferred embodiment, the lignin-based self-healing thermoelectric hydrogel is placed in a cylindrical quartz mold for in-situ molding.
[0068] Furthermore, the electrode is preferably a polyaniline carbon fiber cloth electrode. The polyaniline in the polyaniline carbon fiber cloth electrode can not only enhance the conductivity of the electrode, but also undergo redox reaction.
[0069] Furthermore, the thermoelectric conversion device further comprises a polymer film and a temperature measuring element, and the thermoelectric conversion device comprises a stacked structure arranged in sequence: a temperature measuring element, a polymer film, a first electrode, a thermoelectric conversion material, a second electrode, a polymer film and a temperature measuring element.
[0070] Furthermore, the polymer film includes one or more of a polyimide film (PI film), a polyester film (PET film), a polytetrafluoroethylene film (PTFE film), and a polyurethane film (PU film), preferably a PI film. The use of a polymer film to encapsulate a thermoelectric conversion device can effectively prevent the leakage of solvents, and the polymer film has electrical insulation properties, and can effectively isolate the electrode from the temperature measuring element. Among them, the PI film has excellent electrical insulation properties, can effectively isolate the electrode from the temperature measuring element, and avoid short circuits in the thermoelectric conversion device, so the PI film is preferably used.
[0071] Furthermore, the polyaniline carbon fiber cloth electrode is prepared by a chemical oxidation deposition method, and comprises polyaniline and carbon fiber cloth, wherein the polyaniline is coated on the surface of the carbon fiber cloth.
[0072] Furthermore, the method for preparing the polyaniline carbon fiber cloth electrode comprises the following steps: Aniline monomer and initiator were dissolved in acidic reagents respectively, carbon fiber cloth was immersed in aniline solution, and then the initiator solution was added to the aniline solution to react fully at low temperature, and polyaniline carbon fiber cloth electrode (PANI@CWF) was obtained by post-treatment.
[0073] Furthermore, the initiator is ammonium persulfate and / or potassium persulfate.
[0074] Furthermore, the molar ratio of the aniline monomer to the initiator is 1:(0.25~1).
[0075] Furthermore, the molar ratio of the aniline monomer to the initiator is 1:1.
[0076] Furthermore, the low temperature is an ice water bath.
[0077] Furthermore, the sufficient reaction time is 4 to 16 h, preferably 12 h.
[0078] Furthermore, the post-treatment includes washing and drying.
[0079] Furthermore, the washing is to rinse the carbon fiber cloth electrode containing polyaniline with deionized water for 3 to 6 times.
[0080] Furthermore, the drying is annealing in a vacuum oven at 60-80°C for 2-4 h.
[0081] Specifically, the post-treatment includes rinsing the carbon fiber cloth electrode containing polyaniline with deionized water for 3 times, and then annealing it in a vacuum oven at 60-80° C. for 2-4 h.
[0082] Furthermore, the temperature measuring element is preferably a thermocouple. The temperature measuring element can provide different temperature signals for the thermoelectric conversion device, thereby knowing the thermoelectric conversion efficiency of the thermoelectric conversion device.
[0083] Further, as a preferred embodiment, the method for preparing the thermoelectric conversion device comprises the following steps: The electrode (preferably a polyaniline carbon fiber cloth electrode) is pasted on the bottom surface of a customized circular cylindrical quartz glass (inner diameter 12 mm, outer diameter 16 mm, height 15 mm) mold, and then the lignin-based self-healing thermoelectric hydrogel is poured into the circular cylindrical mold to form it in situ. After forming, another electrode (preferably a polyaniline carbon fiber cloth electrode) is used to paste the upper top surface of the cylindrical mold, and then two polymer films (preferably PI films) are used to attach them to the electrodes on both sides respectively, and finally a temperature measuring element is attached to the polymer films on both sides, which is a thermoelectric conversion device. The assembled thermoelectric conversion device structure is a temperature measuring element, a polymer film, a first electrode, a lignin-based self-healing thermoelectric hydrogel, a first electrode, a polymer film, and a temperature measuring element.
[0084] The present invention protects the application of the above-mentioned lignin-based self-repairing thermoelectric hydrogel or the above-mentioned thermoelectric conversion device in the field of wearable thermoelectric devices, the field of the Internet of Things, and the field of sensing.
[0085] Compared with the prior art, the present invention has the following beneficial effects: The present invention successfully prepared a self-healing thermoelectric hydrogel based on lignin by compounding a specific inorganic small molecule thermoelectric material with cyclodextrin modified lignin sulfonate and adamantyl acrylate. In the formation process of the thermoelectric hydrogel, the inorganic small molecule thermoelectric material is evenly dispersed in the network structure of the hydrogel, giving it excellent mechanical properties; the host-guest interaction introduced by the cyclodextrin modified lignin sulfonate gives it excellent self-healing ability; the hydrogel also has good temperature sensitivity; the above characteristics greatly improve the thermal effect, thermoelectric conversion performance and electrochemical performance of the thermoelectric conversion device prepared based on the above thermoelectric hydrogel; and the preparation method of the above thermoelectric hydrogel is simple and easy, the conditions are mild, the raw materials are easily available, and it has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0086] Figure 1 is a comparison diagram of the hydrogels prepared in Example 1 and Comparative Examples 2 to 6; Figure 2 is a SEM image of the hydrogel prepared in Example 1; Figure 3 1 is the tensile stress-strain curve of the hydrogel prepared in Example 1 and Comparative Example 1; Figure 4 is a self-repairing performance diagram of the hydrogel prepared in Example 1 and Comparative Example 1; Figure 5 is an optical image of the phase transition of the hydrogel prepared in Example 1; Figure 6 is the transmittance-temperature curve of the hydrogel prepared in Example 1; Figure 7 (a) mass change curve and (b) antifreeze optical image of the hydrogel prepared in Example 2; Figure 8 is a SEM image of the polyaniline carbon fiber cloth electrode prepared in Example 1; Fig. 9 is a digital image of the polyaniline carbon fiber cloth electrode prepared in Example 1; Fig.10 is a cyclic voltammetry curve of the polyaniline carbon fiber cloth electrode prepared in Example 1; Fig.11 is a schematic diagram of the structure of the thermoelectric conversion device prepared in Examples 1 to 3; Fig.12 is the open circuit voltage-time curve of the thermoelectric conversion devices prepared in Examples 1-2 and Comparative Examples 7-8; Fig.13 1 is the power density-time curve of the thermoelectric conversion device prepared in Examples 1-2 and Comparative Example 8; Fig.14 It is the specific capacitance curve calculated at different current densities of the thermoelectric conversion devices prepared in Examples 1-2 and Comparative Example 8. DETAILED DESCRIPTION
[0087] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0088] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0089] Unmodified lignin was provided by Zhejiang Jiefa Technology Co., Ltd.
[0090] Figure 7 a means Figure 7 Figure a in the figure; Figure 7 b means Figure 7 The naming of other figures is similar.
[0091] Example 1 Preparation of a self-repairing thermoelectric hydrogel and thermoelectric conversion device based on lignin 1. Preparation of Cyclodextrin-modified Lignin Sulfonate (LS-CD) 36.3 g of β-cyclodextrin and 6.67 g of 1-toluenesulfonyl imidazole were added to 250 mL of deionized water and stirred vigorously at room temperature for 3 h. After adding 50 mL of 10wt% NaOH solution, stirring was continued for 30 min. The unreacted insoluble matter was removed by filtration, and then 1 M HCl solution was added to adjust the pH value of the filtrate to pH = 7.5. The obtained mixture was precipitated at low temperature for 18 h, and then filtered to collect the filter residue, which was washed with ice water and acetone three times to obtain a crude product. The crude product was recrystallized in hot water three times to obtain the product CDOTs. 6.5 g of lignin sulfonate was dissolved in 150 mL of deionized water and stirred thoroughly to obtain a clear solution. 6.5 g of CDOTs was added, and the mixture was stirred vigorously at room temperature for 2 h, then heated to 80 °C and refluxed for 72 h. After cooling, it was transferred to the dialysis bag of MWC 3500 for 3 days, and the retained solution after dialysis was freeze-dried to obtain a yellow or light yellow product, which was LS-CD.
[0092] 2. Preparation of Adamantyl Acrylate (ADA) 3.04 g of 1-adamantanol and 60 mL of anhydrous dichloromethane were added to the reactor and stirred until fully dissolved, then 3 g of triethylamine was added. The mixed solution was kept stirring at 0 °C for 40 min. 3.62 g of acryloyl chloride diluted with 25 mL of anhydrous dichloromethane was added dropwise to the mixed solution at 0 °C through a constant pressure dropping funnel. After the dropwise addition, the mixture was slowly warmed to room temperature and continued to stir for 18 h. After the addition, the insoluble matter was filtered out and the filtrate was collected; the filtrate was washed three times with 0.1 M HCl aqueous solution, 0.5 wt% NaHCO3 solution, and distilled water, respectively, and the organic phase was collected and concentrated by low-temperature vacuum rotary evaporation at 4 °C. It was purified by column chromatography, in which the eluent was V 乙酸乙酯 :V 正己烷 =1:15, and the product ADA was obtained, which was stored at low temperature for future use.
[0093] 3. Preparation of Lignin-based Self-healing Thermoelectric Hydrogel (LAM-1) 0.0144 g LS-CD and 80 μL methanol solution containing ADA (0.01 g / ml) were added to 7 mL of 1.5 mol / L lithium chloride solution (i.e., lithium chloride aqueous solution) and stirred at room temperature for 30 min. Then 0.02 g stannous chloride (SnCl2) was added, followed by 0.96 g acrylamide (AM) and 0.96 g acrylic acid (AA), and finally 0.024 g ammonium persulfate (APS) to obtain the hydrogel LAM-1.
[0094] 4. Preparation of polyaniline carbon fiber cloth electrode First, the carbon fiber cloth (CWF) was ultrasonically cleaned with ethanol and deionized water for 30 min. Then, 0.025 mol of ANI monomer was dissolved in 2.0 mol / L H2SO4 solution (25 mL) by magnetic stirring and reacted in an ice-water bath for 1 h to obtain solution A. Then, 0.025 mol of APS was dissolved in 2.0 mol / L H2SO4 solution (25 mL) to prepare solution B. The cleaned CWF was used as a supporting substrate, and polyaniline nanorod arrays were directly assembled on it by a simple chemical oxidation deposition process. The CWF was vertically immersed in solution A, and then solution B was added to solution A and reacted in an ice-water bath with magnetic stirring for 12 h. The obtained CWF containing polyaniline was rinsed with deionized water several times and then annealed in a vacuum oven at 60 ℃ for 2 h to finally obtain the product, which was labeled as polyaniline carbon fiber cloth electrode (PANI@CWF).
[0095] 5. Preparation of Thermoelectric Conversion Devices The PANI@CWF electrode was pasted to the bottom surface of the customized cylindrical quartz mold (inner diameter 12 mm, outer diameter 16 mm, height 15 mm), and the LAM-1 hydrogel was poured into the circular column mold to form it in situ. After forming, another PANI@CWF electrode was pasted to the top surface of the cylindrical mold of the mold, and two PI films were attached to the electrodes on both sides respectively. Finally, thermocouples were attached to the polymer films on both sides to form a thermoelectric conversion device.
[0096] Example 2 Preparation of a self-repairing thermoelectric hydrogel and thermoelectric conversion device based on lignin The difference from Example 1 is that the solvent of the lithium chloride solution in step 3 is changed from water to glycerol / water, wherein V 甘油 :V 水 =1:2.
[0097] The other steps and conditions are the same as those in Example 1, and the lignin-based self-repairing thermoelectric hydrogel LAM-2 and the thermoelectric conversion device prepared based on LAM-2 are obtained in sequence.
[0098] Example 3 Preparation of a self-repairing thermoelectric hydrogel and thermoelectric conversion device based on lignin The difference from Example 1 is that the inorganic small molecule thermoelectric material lithium chloride in step 3 is replaced by sodium chloride.
[0099] The other steps and conditions are the same as those in Example 1, and the lignin-based self-repairing thermoelectric hydrogel LAM-3 and the thermoelectric conversion device prepared based on LAM-3 are obtained in sequence.
[0100] Comparative Example 1 Preparation of a thermoelectric hydrogel based on lignin The difference from Example 1 is that the cyclodextrin-modified lignin sulfonate in step 1 is replaced by commercially available unmodified lignin.
[0101] The other steps and conditions were the same as those in Example 1 to obtain the lignin-based self-repairing thermoelectric hydrogel LAM-4.
[0102] Comparative Example 2 Preparation of a self-repairing thermoelectric hydrogel based on lignin The difference from Example 1 is that the inorganic small molecule thermoelectric material lithium chloride in step 3 is replaced by lithium bromide.
[0103] The other steps and conditions were the same as those in Example 1 to obtain the lignin-based self-repairing thermoelectric hydrogel LAM-5.
[0104] Comparative Example 3 Preparation of a self-repairing thermoelectric hydrogel based on lignin The difference from Example 1 is that the inorganic small molecule thermoelectric material lithium chloride in step 3 is replaced by potassium iodide.
[0105] The other steps and conditions were the same as those in Example 1 to obtain the lignin-based self-repairing thermoelectric hydrogel LAM-6.
[0106] Comparative Example 4 Preparation of a self-repairing thermoelectric hydrogel based on lignin The difference from Example 1 is that the inorganic small molecule thermoelectric material lithium chloride in step 3 is replaced by potassium bromide.
[0107] The other steps and conditions were the same as those in Example 1 to obtain the lignin-based self-repairing thermoelectric hydrogel LAM-7.
[0108] Comparative Example 5 Preparation of a self-repairing thermoelectric hydrogel based on lignin The difference from Example 1 is that the inorganic small molecule thermoelectric material lithium chloride in step 3 is replaced by sodium iodide.
[0109] The other steps and conditions were the same as those in Example 1 to obtain the lignin-based self-repairing thermoelectric hydrogel LAM-8.
[0110] Comparative Example 6 Preparation of a self-repairing thermoelectric hydrogel based on lignin The difference from Example 1 is that the inorganic small molecule thermoelectric material lithium chloride in step 3 is replaced by sodium bromide.
[0111] The other steps and conditions were the same as those in Example 1 to obtain the lignin-based self-repairing thermoelectric hydrogel LAM-9.
[0112] Comparative Example 7 Preparation of a self-repairing thermoelectric hydrogel and thermoelectric conversion device based on lignin The difference from Example 1 is that the inorganic small molecule thermoelectric material lithium chloride in step 3 is not added.
[0113] The other steps and conditions were the same as those in Example 1, and the lignin-based self-repairing thermoelectric hydrogel LAM-10 and the thermoelectric conversion device prepared based on LAM-10 were obtained in sequence.
[0114] Comparative Example 8 Preparation of a self-repairing thermoelectric hydrogel and thermoelectric conversion device based on lignin The difference from Example 1 is that the addition method of the inorganic small molecule thermoelectric material lithium chloride in step 3 is changed from the integration method to the replacement method, and the lignin-based self-repairing thermoelectric hydrogel LAM-11 and the thermoelectric conversion device prepared based on LAM-11 are obtained in turn. The specific preparation method includes the following steps: 1. Preparation of Cyclodextrin-modified Lignin Sulfonate (LS-CD) 36.3 g of β-cyclodextrin and 6.67 g of 1-toluenesulfonyl imidazole were added to 250 mL of deionized water and stirred vigorously at room temperature for 3 h. After adding 50 mL of 10wt% NaOH solution, stirring was continued for 30 min. Unreacted insoluble matter was removed by filtration, and then 1 M HCl solution was added to adjust the pH value of the filtrate to pH = 7.5. The obtained mixture was precipitated at low temperature for 18 h, and then filtered to collect the filter residue, which was washed with ice water and acetone three times to obtain a crude product. The crude product was recrystallized in hot water three times to obtain the product CDOTs. 6.5 g of lignin sulfonate was dissolved in 150 mL of deionized water and stirred thoroughly to obtain a clear solution. 6.5 g of CDOTs was added, stirred vigorously at room temperature for 2 h, and then heated to 80 °C and refluxed for 24 h. After cooling, it was transferred to the dialysis bag of MWC 3500 for 3 days, and the retained solution after dialysis was freeze-dried to obtain a yellow or light yellow product, which was LS-CD.
[0115] 2. Preparation of Adamantyl Acrylate (ADA) 3.04 g of 1-adamantanol and 60 mL of anhydrous dichloromethane were added to the reactor and stirred until fully dissolved, then 3 g of triethylamine was added. The mixed solution was kept stirring at 0 °C for 40 min. 3.62 g of acryloyl chloride diluted with 25 mL of anhydrous dichloromethane was added dropwise to the mixed solution at 0 °C through a constant pressure dropping funnel. After the dropwise addition, the mixture was slowly warmed to room temperature and continued to stir for 18 h. After the addition, the insoluble matter was filtered out and the filtrate was collected; the filtrate was washed three times with 0.1 M HCl aqueous solution, 0.5 wt% NaHCO3 solution, and distilled water, respectively, and the organic phase was collected and concentrated by low-temperature vacuum rotary evaporation at 4 °C. It was purified by column chromatography, in which the eluent was V 乙酸乙酯 :V 正己烷 =1:15, and the product ADA was obtained, which was stored at low temperature for future use.
[0116] 3. Preparation of Lignin-based Self-healing Thermoelectric Hydrogel (LAM-11) 0.0144 g LS-CD and 80 μL methanol solution containing ADA (0.01 g / ml) were added to 7 mL ultrapure water and stirred at room temperature for 30 min. Then 0.02 g stannous chloride (SnCl2) was added, followed by 0.96 g acrylamide (AM) and 0.96 g acrylic acid (AA), and finally 0.024 g ammonium persulfate (APS) to obtain P(AA-AM) hydrogel. Finally, the P(AA-AM) hydrogel was soaked in 1.5 mol / L lithium chloride aqueous solution to obtain hydrogel LAM-11.
[0117] 4. Preparation of polyaniline carbon fiber cloth electrode First, carbon fiber cloth (CWF) was ultrasonically cleaned with ethanol and deionized water for 30 min. Then, 0.025 mol of ANI monomer was dissolved in 2.0 mol / L H2SO4 solution (25 mL) by magnetic stirring and reacted in an ice-water bath for 1 h to obtain solution A. Then, 0.025 mol of APS was dissolved in 2.0 mol / L H2SO4 solution (25 mL) to prepare solution B. The cleaned CWF was used as a supporting substrate, and polyaniline nanorod arrays were directly assembled on it by a simple chemical oxidation deposition process. CWF was vertically immersed in solution A, and then solution B was added to solution A and reacted in an ice-water bath with magnetic stirring for 12 h. The obtained CWF containing polyaniline was rinsed with deionized water several times and then annealed in a vacuum oven at 60 ℃ for 2 h to finally obtain the product, which was labeled as PANI@CWF.
[0118] 5. Preparation of Thermoelectric Conversion Devices The PANI@CWF electrode was pasted to the bottom surface of the customized cylindrical quartz mold (inner diameter 12 mm, outer diameter 16 mm, height 15 mm), and the LAM-11 hydrogel was poured into the circular column mold to form it in situ. After forming, another PANI@CWF electrode was pasted to the top surface of the cylindrical mold, and two PI films were attached to the electrodes on both sides, and finally the thermocouples were attached to the polymer films on both sides, which was the thermoelectric conversion device.
[0119] Experimental Example 1 Performance Characterization of Thermoelectric Hydrogel and Electrode (1) Physical picture of hydrogel By comparing the hydrogels in Example 1 and Comparative Examples 2 to 6, Figure 1 As shown in the figure, the precursor solution with lithium chloride added in Example 1 formed a hydrogel network structure. However, in Comparative Examples 2 to 6, the precursor solutions with lithium bromide, potassium iodide, potassium bromide, sodium iodide and sodium bromide added failed to form a network structure. This may be because the iodide ion (I - ) and bromide ion (Br - ) has a larger ionic radius than the chloride ion (Cl - ), which may affect the arrangement of polymer chains and the cross-linking structure, resulting in the inability to form a stable three-dimensional network.
[0120] (2) SEM image of hydrogel The hydrogel in Example 1 was characterized by SEM. Figure 2 As shown in the figure, at low temperatures, there are a large number of inter-chain / intra-chain hydrogen bonds between carboxyl groups (-COOH) and amide groups (-CONH2) in the hydrogel network. This molecular action causes the polymer chains to aggregate, and this aggregation behavior in turn causes the hydrogel system to form a "sieve-like" network. Under the temperature gradient provided by the temperature measuring element (thermocouple) (the hot end temperature is 318 K and the cold end temperature is 298 K), a temperature difference will be generated inside the hydrogel, and the size of its pores will increase with the increase of temperature, that is, it has volume phase transition behavior. Among them, due to the negative charge of carboxyl / amino groups in the hydrogel, the hydrogel network can gradually suppress the large-sized Cl in lithium chloride (LiCl) through electrostatic repulsion. - Heat diffusion towards the hot end, and Li + The volume is smaller, and the relative fluidity and diffusion rate are higher than Cl - Big, so Li + will migrate from the hot end to the cold end. + and Cl - They are respectively gathered in the cold end direction and the hot end direction on both sides of the hydrogel, thereby generating thermoelectric potential, which can further enhance the ionic Seebeck coefficient of the prepared thermoelectric material.
[0121] (3) Mechanical properties test The hydrogels were tensile tested at room temperature using a microcomputer-controlled universal testing machine (CMT6203; SensTest, Shenzhen, China) with a 100 N load cell; the tensile strain capacity of the hydrogels was tested by uniaxial tensile testing, i.e., the hydrogel samples were cut into rectangles with a thickness of about 2 mm, a length of about 15 mm, and a width of about 4 mm, and stretched at a tensile speed of 50 mm / min, with four equilibrium samples measured for each group of samples. The mechanical properties of the hydrogels were compared by comparing the tensile strength and tensile strain capacity of the hydrogels in Example 1 with those in Comparative Example 1, as shown in FIG. Figure 3 As shown, compared with the LAM-4 hydrogel in Comparative Example 1 (tensile strength 119 kPa and tensile strain 802%), the tensile strength of the LAM-1 hydrogel to which LS-CD was added in Example 1 reached 264 kPa, and the tensile strain reached 1208%, which indicates that the thermoelectric hydrogel in Example 1 has excellent mechanical properties.
[0122] (4) Self-healing performance test The self-repairing performance was compared by comparing the contact bearing capacity of the hydrogel cross section in Example 1 with that in Comparative Example 1. Figure 4 As shown, the LAM-1 hydrogel prepared in Example 1 can still withstand 175% stretching without breaking after the cross-section contact self-repair for 1 hour, while the LAM-4 hydrogel prepared in Comparative Example 1 cannot withstand stretching after the cross-section contact self-repair for 1 hour. This proves that after introducing the host-guest interaction, the LAM-1 hydrogel prepared in this application has a more superior self-healing performance (5) Temperature sensitivity test The upper critical eutectic temperature (UCST) of the hydrogel was determined by using an ultraviolet-visible spectrophotometer (UV-VIS) and an ultra-constant temperature water bath to characterize the thermosensitive properties of the hydrogel. The transmittance of the hydrogel sample was measured in the range of 298~368 k by placing the hydrogel sample to be tested in a UV-visible spectrophotometer with a constant temperature water bath. The wavelength parameter of the UV-visible spectrophotometer was set to 600 nm, and the range parameter of the measuring light was 3 cm. After each temperature increase, the next temperature increase was carried out after the sample transmittance stabilized, and the temperature and transmittance curve was prepared. Figure 5 As shown, the LAM-1 hydrogel in Example 1 can switch between white opaque and transparent states in the temperature range of 278 to 318 K, which preliminarily proves that the hydrogel has phase transition behavior; to further explore the temperature sensitivity of the hydrogel, the LAM-1 hydrogel was subjected to in-situ variable temperature UV detection, and the phase transition temperature is 50% of the transmittance of the LAM hydrogel during the heating process, as shown in FIG. Figure 6As shown in the figure, during the test, as the temperature increases, the transmittance increases, and the transmittance is 50% at 325 K. The critical solution temperature (UCST) is 313 K, indicating that when the LAM-1 hydrogel sample is below 313 K (278 K), hydrogen bonds are formed between the amide and carboxyl groups in the hydrogel sample, the molecular chains shrink, the gel dehydrates and becomes turbid; when the temperature is above 313 K (318 K), the hydrogen bonds between the amide and carboxyl groups open, the gel absorbs water and becomes transparent, and the temperature sensitivity of the thermoelectric conversion material provides a way to construct a gradient ion channel.
[0123] (6) Antifreeze and water retention performance test The antifreeze and water retention performance of the hydrogel in Example 2 was tested. Figure 7 As shown in a, after being stored at 25 °C for 7 days, LAM-2 hydrogel can still maintain more than 70% of its initial weight. In order to study the antifreeze properties of LAM-2 hydrogel. Figure 7 As shown in Figure b, we verified the conductivity of the hydrogel under low temperature conditions. Whether at room temperature or -20 °C, the small light bulb in the hydrogel circuit can still remain lit, proving that it can still maintain electron transmission under low temperature conditions. This shows that adding glycerol as a solvent in the preparation of the hydrogel can make it have good antifreeze and water retention properties.
[0124] (7) Morphology of polyaniline carbon fiber cloth electrode like Figure 8 As shown in the figure, a layer of dark green deposits was observed on the polyaniline carbon fiber cloth electrode (PANI@CWF) prepared in Example 1, which well covered the CWF electrode below. Fig. 9 As shown, a dense nanorod array is formed on the surface of PANI@CWF. The formation of the nanorod array significantly increases the surface area of the electrode, thereby increasing the contact area between it and the thermoelectric material and enhancing the electrochemical performance of the electrode.
[0125] (8) Electrochemical properties of polyaniline carbon fiber cloth electrodes The PANI@CWF electrode prepared in Example 1 was characterized by cyclic voltammetry curves at different scan rates in 1 M H2SO4 solution using a two-electrode test system. Fig.10 As shown, the results show that with the increase of scan rate, the oxidation peak and reduction peak of PANI@CWF electrode move to positive and negative potentials, respectively, indicating that the electrode has good reversibility and fast charge and discharge response.
[0126] Experimental Example 2 Performance Characterization of Thermoelectric Conversion Devices (1) Structural diagram The schematic diagram of the structure of the thermoelectric conversion device prepared in Examples 1 to 3 is as follows Fig.11 As shown, the overall stacked structure is arranged in sequence, from bottom to top: thermocouple, PI film, polyaniline carbon fiber cloth electrode (PANI@CWF), lignin-based self-healing thermoelectric hydrogel, polyaniline carbon fiber cloth electrode, PI film and thermocouple.
[0127] (2) Thermal effect The thermal effect was measured on an electrochemical workstation (Bio-logic-VMP-3e) and an integrated instrument with a temperature controller (TLTP-TEC2415D) with a temperature deviation of ±0.1 K. The temperature gradient was set, thermal charging was performed, and the change in thermovoltage was recorded using the electrochemical workstation until the thermovoltage equilibrium was stable and the open circuit voltage was recorded at this time; after measuring the saturation voltage under different temperature gradients, the ion Seebeck coefficient was calculated by the formula S i =△ V / △ T By comparing the open circuit voltage and Seebeck coefficient of the thermoelectric conversion devices in Examples 1-2 and Comparative Examples 7-8, the thermal effect of the thermoelectric conversion device is characterized, such as Fig.12 As shown in Figure 2, under the condition of a temperature difference of 20 K, the thermoelectric conversion device of Comparative Example 7 exhibits a maximum open circuit voltage of 0.2 V and a Seebeck coefficient of 10 mV•K -1 The thermoelectric conversion device of Comparative Example 8 shows an open circuit voltage of up to 0.109 V and a Seebeck coefficient of 5.45 mV•K -1 The "sandwich" structure thermoelectric conversion device composed of the LAM hydrogel prepared in Example 1 and the polyaniline carbon fiber cloth electrode showed a maximum open circuit voltage of 0.395 V and a Seebeck coefficient of 19.75 mV•K under the same temperature difference conditions. -1 The thermoelectric conversion device of Example 2 shows an open circuit voltage of up to 0.404 V and a Seebeck coefficient of 20.2 mV•K -1 , which strongly proves that the addition of lithium chloride can significantly improve the thermal effect of thermoelectric conversion devices.
[0128] (3) Thermoelectric conversion performance The energy density of the thermoelectric conversion devices in Examples 1-2 and Comparative Example 8 was tested to characterize their thermoelectric conversion performance, using ≤0.3 mV min -1 The voltage is close to saturation state by defining the voltage change rate. Then, the power output level is obtained by externally connecting various resistors, and the energy density during the 1-hour discharge process is calculated by integrating the output power curve, and P=E / Δ t The average power density under external load is calculated by the equation, where ∆ tis the total duration of the discharge phase in a thermal cycle, and the instantaneous output power is obtained by multiplying the voltage and current. Fig.13 As shown in the figure, under the condition of a temperature difference of 20 K, the power-time curves of the thermoelectric conversion devices of Examples 1-2 and Comparative Example 8 connected in series with a 3 kΩ resistor box are shown, wherein the energy density of Comparative Example 8 within 1 h is 117.4 J•m -2 , while Examples 1 and 2 can reach 616.04 J•m -2 and 676 J•m -2 , indicating that only when specific inorganic small molecule thermoelectric materials are directly prepared into thermoelectric hydrogels and then integrated with polyaniline carbon fiber cloth electrodes to prepare the resulting thermoelectric conversion devices can they have excellent thermoelectric conversion performance.
[0129] (4) Electrochemical performance Cyclic voltammetry (CV) tests first set a voltage window (0-1 V), test the electrode at different scan rates, repeatedly scan with a triangular waveform over time, and record the current-potential curve. The electrochemical performance of the thermoelectric conversion device is reflected by comparing the maximum specific area capacitance of Examples 1-2 and Comparative Example 8. Fig.14 As shown, the maximum specific area capacitance of the thermoelectric conversion device of Comparative Example 8 is 76 mF•cm -2 , while Examples 1 and 2 can reach 764 mF•cm -2 and 355 mF•cm -2 , indicating that compared with the solution replacement method commonly used in existing research (i.e. preparing gel first and then replacing it with LiCl), the advantage of directly using LiCl solution to prepare gel is that it can be directly poured into the device and combined with the polyaniline carbon fiber cloth electrode to achieve "integration" when the gel is still in the precursor solution state. This method effectively solves the problem of poor contact between the thermoelectric gel and the electrode, ensuring that the thermoelectric conversion device prepared in this application has better interface contact and electrochemical performance.
[0130] In summary, the present invention successfully prepared a lignin-based self-healing thermoelectric hydrogel by compounding a specific inorganic small molecule thermoelectric material with cyclodextrin-modified lignin sulfonate and adamantyl acrylate. During the formation of the thermoelectric hydrogel, the inorganic small molecule thermoelectric material is evenly dispersed in the network structure of the hydrogel, giving it excellent mechanical properties; the host-guest interaction introduced by the cyclodextrin-modified lignin sulfonate gives it excellent self-healing ability; the hydrogel also has good temperature sensitivity; the above characteristics greatly improve the thermal effect, thermoelectric conversion performance and electrochemical performance of the thermoelectric conversion device prepared based on the above thermoelectric hydrogel.
[0131] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a self-repairing thermoelectric hydrogel based on lignin, characterized in that: The following steps are involved: Cyclodextrin-modified lignin sulfonate and adamantyl acrylate are added to a solvent containing an inorganic small molecule thermoelectric material and mixed evenly, and unsaturated carboxylic acid monomers, acrylamide monomers, metal ions and initiators are added to fully react to prepare a lignin-based self-healing thermoelectric hydrogel; Wherein, the inorganic small molecule thermoelectric material is selected from one or more of lithium chloride, sodium chloride and potassium chloride.
2. The preparation method according to claim 1, characterized in that: The concentration of the inorganic small molecule thermoelectric material is 0.1-3 mol / L.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the cyclodextrin modified lignin sulfonate to adamantyl acrylate is (1-75):
1.
4. The preparation method according to claim 1, characterized in that: The metal ions are derived from one or more of stannous chloride, ferric chloride, calcium chloride, barium chloride, aluminum chloride, cobalt chloride, nickel chloride, cupric chloride, and silver chloride.
5. The preparation method according to claim 1, characterized in that: The unsaturated carboxylic acid monomer is C3-C8 olefinic acid and / or C3-C8 acetylenic acid.
6. The preparation method according to claim 1, characterized in that: The acrylamide monomers include one or more of acrylamide, methacrylamide, and ethyl acrylamide.
7. The lignin-based self-repairing thermoelectric hydrogel prepared by the preparation method according to any one of claims 1 to 6.
8. A thermoelectric conversion device, characterized in that: The thermoelectric conversion device comprises the lignin-based self-healing thermoelectric hydrogel according to claim 7 and an electrode; the lignin-based self-healing thermoelectric hydrogel is connected to the electrode as a thermoelectric conversion material.
9. The thermoelectric conversion device according to claim 8, characterized in that: The thermoelectric conversion device includes a stacked structure arranged in sequence: a first electrode, a thermoelectric conversion material, and a second electrode.
10. Application of the lignin-based self-repairing thermoelectric hydrogel according to claim 7 or the thermoelectric conversion device according to claim 8 or 9 in the field of wearable thermoelectric conversion devices, the Internet of Things, and the sensing field.
Citation Information
Patent Citations
Gel electrode, full-gel-state ion thermoelectric supercapacitor and preparation of full-gel-state ion thermoelectric supercapacitor
CN111564316A
Thermoelectric conversion material, thermoelectric conversion device and preparation method and application thereof
CN115895158A
Cyclodextrin modified lignosulfonate and application thereof in friction nano generator
CN117586513A
Lignin-containing self-repairing hydrogel capable of being self-assembled as well as preparation method and application of lignin-containing self-repairing hydrogel
CN117903381A
Polarizing film with added adhesive layer, polarizing film with added adhesive layer for in-cell liquid crystal panel, in-cell liquid crystal panel, and liquid crystal display device
US20210108109A1